Single-Lab Validation for Determination of Kavalactones and Flavokavains in Piper methysticum (Kava) - Liu, Ying; Lund, Jensen A.; Murch, Susan J.; Brown, Paula N. (Planta Medica, 2018)
Piper methysticum (Kava) is a plant whose roots are used in the preparation of traditional beverages with spiritual, medicinal, and social importance for the Pacific Islanders. Kava is also sold as a herbal supplement or recreational beverage consumed for its mild inebriating effect in Europe and North America. With an ongoing interest in the safety and quality of kava products, it is necessary to develop a validated method for determination of kava chemical composition to ensure confidence in quality assessment. Thus, an high-performance liquid chromatography with ultraviolet detection (HPLC-UV) method was developed, optimized, and validated for determining six major kavalactones and three flavokavains in kava raw materials and finished products based on AOAC single-laboratory validation guidelines. This is the first fully validated analytical method for measuring kavalactones and flavokavains in a single run. The separation of the analytes was achieved in 10 min with an Agilent Poroshell C18 column using gradient separation. The sample was extracted with methanol first and then acetone. The signals were detected at 240 nm and 355 nm. The limit of quantification was under 1.2 µg/mL (0.3 mg/g) for kavalactones and under 0.35 µg/mL (0.01 mg/g) for flavokavains. The Horwitz ratio values described ranged from 0.3 to 1.82. The spike recovery experiments showed an accuracy between 92 and 105% for all analytes. The results of the study demonstrate that the method is fit for the purpose of determining methysticin, dihydromethysticin, kavain, dihydrokavain, yangonin, desmethoxyyangonin, flavokavain A, flavokavain B, and flavokavain C in kava raw material and finished products (dry-filled capsule, liquid phytocaps, and tincture).
Keywords: kava; Piper methysticum; kavalactones; flavokavains; HPLC-UV; single-laboratory validation; Piperaceae; quality control